(untitled) (Research, Society and Development, 2021)
Introduction: Breast milk is the main and the best source of food for a child who is in the development stage. However, when a baby goes to a neonatal intensive care unit, it is very common for the mother to have difficulty offering breast milk due to several factors. Objective: To identify the factors that hinder breastfeeding in the Neonatal ICU. Methodology: This is an integrative literature review carried out between September and October 2020 in the databases: Nursing Database (BDENF), Latin American and Caribbean Literature on Health Sciences (LILACS) and Online System of Search and Analysis of Medical Literature (MEDLINE), with articles published between the years 2015 to 2019. Results: The search revealed eight articles to compose the study, from 2015 to 2019, available in full in English and Portuguese. The main categories found were: Mothers’ feelings about the newborn admitted to the NICU, maternal experiences related to breastfeeding in a NICU and the importance of support from the professional team and the family related to breastfeeding. Final Considerations: It was possible to analyze that in a setting of a NICU there are several weaknesses in relation to breastfeeding, among them are: The lack of support from professionals, negative feelings of mothers and their experiences related to the act of breastfeeding. It is very important that the health professional be cautious, supportive and a facilitator so that this mother remains firm in the care of her baby.